Whiplash Injuries: An Update - Robert W Teasell; Allan P Shapiro (Pain Research and Management)
Whiplash injuries remain a significant public health problem throughout the developed industrialized world, with significant socioeconomic consequences. Studies looking at the natural history of whiplash injuries have suffered from problems of selection bias, retrospective reviewing and unclear outcomes. Etiology continues to be controversial, largely because of the misconception that all soft tissue injuries heal within six weeks. Recent studies have implicated the cervical facet joint as a cause of whiplash injury pain. A recent treatment study that successfully eliminated whiplash-associated facet joint pain demonstrated abnormal psychological profiles secondary to pain which normalized with successful pain elimination. The impact of compensation on recovery remains controversial, while the concept that mild traumatic brain injury occurs in the absence of loss of consciousness has been largely refuted. The Quebec Task Force on Whiplash-Associated Disorders recently published a report in which the scientific literature was exhaustively reviewed and has made recommendations regarding the prevention and treatment of whiplash and its associated disorders. The Quebec Task Force highlighted the paucity of good scientific evidence; however, they still provided consensus treatment guidelines, which have not been validated. There continues to be a need for further research.